Active galactic nuclei: global perspective and time-domain implications - Kazanas, Demosthenes (Frontiers in Astronomy and Space Sciences, 2024)
A view of the global structure of active galactic nuclei (AGN) is presented herein following the detection of blue-shifted warm absorber (WA) and ultrafast outflow (UFO) absorption features in their X-ray spectra. A straightforward interpretation of these features suggests the presence of magnetohydrodynamic winds off the underlying accretion disks spanning a wide range of a few to ∼106 Schwarzschild radii. UFOs are associated with wind segments closest to a black hole, with decreasing ionization absorber species associated with these wind segments at increasingly larger distances; eventually, the wind segments at the largest distances are sufficiently cool and dusty to be associated with the AGN tori, as suggested in the past. Furthermore, spectroscopic X-ray observations at a sufficient resolution allow estimates of the mass fluxes of these winds, showing that they increase with radius. As a consequence, the mass flux of the underlying accretion disk must decrease toward the accreting black hole, eventually reaching a value smaller than that needed to convert the flow into an X-ray hot advection-dominated accretion flow; it is suggested that this hot segment of the accretion flow is responsible for the observed AGN X-rays (and galactic X-ray binaries) in place of the ad hoc corona assumed thus far. This work indicates that the properties of this component that are reflected in its relative luminosity to the viscous disk O-UV component depend on the source luminosity in broad agreement with the observations.